Pengaruh Konsentrasi Gliserol dalam Edible Coating Tepung Biji Nangka dengan Penambahan Plasticizer Gliserol - Emmanuela Maria Widyanti; Nancy Siti Djenar; Ari Marlina; Endang Widiastuti; Irwan Hidayatulloh; Intan Puspitarini; Dhara Firdausa; Lidya Elizabeth (Fluida, 2022)
Tomatoes are horticultural plants that are easily damaged, need to be coated with a food grade edible coating. The basic ingredients that can be used are polysaccharides, derived from jackfruit seed flour, then glycerol plasticizer is added to improve the brittle nature of the edible coating. The maximum glycerol added was carried out with the following concentration variations: control (without glycerol), 1.5%, 2.0%, 2.5%. The analysis carried out included testing the respiration rate and weight loss in tomato storage for 6 days. In determining the respiration rate, an experiment was carried out by flowing 1 L/minute of air for 2 minutes which had been passed through a saturated Ca(OH)2 solution flowed into a jar containing tomatoes, passing through a 0.05 N NaOH solution added 0.1% phenophthalein indicator and titrated with HCl 0.05 N until the red color disappears and the weight loss decreases on tomatoes coated with edible coating. The results obtained were the lowest decrease in respiration rate at 2% glycerol concentration of 0.137 mgCO2/kg.hour and the lowest decrease in weight loss at 2.5% glycerol concentration of 1.913%.